Quality characteristics of meat from triceps brachii muscle from steers and heifers finished on high-concentrate diets containing increasing concentrations of linseed oil - Oliveira, E. A. [UNESP]; Sampaio, A. A.M. [UNESP]; Rosa, B. L. [UNESP]; Henrique, W.; Pivaro, T. M.; Carvalho, V. G. [UNESP]; Cirne, L. G.A. [UNESP]; Duckett, S. K. (CSIRO Publishing, 2017)
The aim of the present study was to assess the qualitative and chemical characteristics of a shoulder muscle (triceps brachii muscle, medial head (TBm)) of 15 Nellore × Canchim steers and 14 heifers of the same cross fed diets containing 80% concentrate on a dry-matter (DM) basis and increasing concentrations of linseed oil (1%, 3.8% and 5.2% of DM). A randomised incomplete-block design, divided on the basis of initial bodyweight, in a 3 × 2 factorial scheme (oil concentration and animal sex) was used. Oil concentrations were evaluated by linear and quadratic regression. The finishing period lasted for 96, 110 or 138 days, until the average weight of each block reached 500 kg. At 24 h postmortem, TBm samples were taken to evaluate quality traits and chemical composition. Meat from steers was significantly (P < 0.05) brighter than was heifer meat (brightness (L∗) = 39.55 vs 36.28). The addition of linseed oil up to 5.2% improved the pH value of TBm in heifers (6.07, 6.22 and 5.77). No significant (P > 0.05) influence was observed for linseed oil addition up to 5.2% of DM or animal sex on the chemical characteristics of TBm, estimated activity of Δ9-desaturase and elongase, and atherogenic and thrombogenic indices. However, the increasing inclusion of linseed oil in the diet of crossbred cattle increased (P < 0.05) conjugated linoleic acid (0.46, 0.66 and 0.73 g/100 g total fatty acids), α-linolenic acid (0.39, 0.69 and 1.31 g/100 g total fatty acids for steers 0.36, 0.79 and 0.76 g/100 g total fatty acids for heifers), γ-linolenic acid (0.07, 0.10 and 0.24 g/100 g total fatty acids), and the sum of n-3 fatty acids. The increasing inclusion of linseed oil also increased the ratio of polyunsaturated fatty acids to saturated fatty acids and decreased the ratio of n-6:n-3 fatty acids (11.68, 6.43 and 5.26 for steers 10.69, 6.93 and 6.03 for heifers). Supplementation of finishing cattle with linseed oil is an effective means to increase n-3 fatty acid concentration in forequarter muscle.
Keywords: beef cattle; fatty acids; hypocholesterolemic; n-3